The Influence of Digital Marketing and Brand Image on Customer Retention on Hospitality Practice with Customer Relationship Marketing (CRM) as a Mediator - Kurniawan, I Nengah; Ruspendi Junaedi, I Wayan; Joko Adinegara, Gusti Ngurah; Budi Santoso, R Tri Priyono (The Es Economics and Entrepreneurship, 2024)
In an increasingly advanced digital era, digital marketing, brand image, and customer relationship marketing have become important elements in a company's marketing strategy. This study aims to analyse the effect of digital marketing and brand image on customer retention at Prasi Hospitality, with customer relationship marketing as a mediating variable. This study involved 70 respondents who were selected using purposive sampling method. Data was collected through questionnaires. To test the hypothesis, data analysis was conducted using SEM-PLS technique using SmartPLS. The results showed that digital marketing and brand image directly have a positive effect on customer retention, and also have an indirect positive effect through customer relationship marketing. Customer relationship marketing can partially mediate the effect of digital marketing and brand image on customer retention. Digital marketing and brand image each have a positive effect on customer relationship marketing, which in turn also has a positive effect on customer retention. It is recommended to develop content that is interactive, provides a personalised experience, and is tailored to customer preferences.